Effect of dipeptidyl peptidase-4 inhibitors on heart failure: A meta-analysis of randomized clinical trials - J. Kongwatcharapong (2018)
© 2016 Elsevier Ireland Ltd. All rights reserved. Background: Recent studies have suggested that dipeptidyl peptidase-4 inhibitors (DPP-4 inhibitors) may be associated with increased risk of heart failure (HF), but evidence was inconclusive. We aimed to determine the effects of DPP-4 inhibitors on risk of HF. Methods: An extensive search in PubMed, EMBASE, CINAHL, IPA, Cochrane, ClinicalTrial.gov and the manufacturers' websites for randomized controlled trials (RCT) of all DPP-4 inhibitors was performed up to June 2015. All RCTs comparing DPP-4 inhibitors to any comparators with minimum follow-up of 12 weeks were included. The primary outcome was the occurrence of HF. Results: A total of 54 studies with 74,737 participants were included for analysis. Overall, DPP-4 inhibitors were not associated with an increased risk of HF compared to comparators (relative risk (RR) 1.106; 95% CI 0.995-1.228; p = 0.062). When analyzed individually, saxagliptin was significantly associated with the increased risk of HF (RR 1.215; 95% CI, 1.028-1.437; p = 0.022), while others were not. Age ≥ 65 years, diabetes duration of ≥ 10 years and BMI ≥ 30 kg/m2were associated with an increased risk of HF among patients using saxagliptin. Conclusions: Our meta-analysis suggested a differential effect of each DPP-4 inhibitor on the risk of HF. Use of saxagliptin significantly increases the risk of HF by 21% especially among patients with high CV risk while no signals were detected with other agents. This information should be taken into consideration when prescribing DDP-4 inhibitors.